Objek Wisata Pemandian Alam Bektiharjo Sebagai Sumber Pembelajaran Biologi - Windhiana Ayu Lestari; Imas Cintamulya (BIOEDUSCIENCE, 2023)
Background: Bektiharjo tourism object is a natural tourism object with abundant potential for biodiversity, unspoiled environmental conditions, and diverse socio-economic interactions of the community. This study aims to describe the use of Bektiharjo tourism objects as a source of learning through studies on the abundance of biodiversity, environmental feasibility conditions, and socio-economic conditions in Bektiharjo tourism objects. Methods: This study uses a quantitative descriptive. The instruments used in this study were observation sheets and questionnaires. Observation sheets can use to obtain data on biodiversity abundance and tourism objects' environmental feasibility conditions. Questionnaires were used to obtain data on the socio-economic conditions of the community. Data is collected with analysis descriptively. Results: The results showed that Bektiharjo tourism object has an abundance of biodiversity in the category of high diversity, high evenness, stable community, and relatively moderate species dominance, environmental feasibility conditions are categorized as excellent, and socio-economic conditions are categorized as excellent. Conclusion: Bektiharjo tourism objects can be a learning resource for biology education students. From the results of this study, it is hoped that it can be an alternative to using tourist objects as a source of learning that various levels of education can use.